Mapping Access Points in the PT PLN (Persero) UIP SUMBAGSEL Archive Building Using NetSpot and WiFi Analyzer - M. Rizky Aulia (Institute of Information Technology and Social Science (IITSS), 2024)
The rapid advancement of information and communication technology in the digital era has significantly transformed connectivity infrastructures, with Wi-Fi networks becoming essential for supporting mobility and facilitating high-speed data access across diverse sectors. As a leading state-owned energy enterprise in Indonesia, PT PLN (Persero) relies heavily on stable and reliable Wi-Fi networks to enhance operational efficiency, enable interdepartmental communication, and support access to corporate information systems throughout its organizational units. However, the Wi-Fi network in the PT PLN (Persero) UIP SUMBAGSEL Archive Building exhibited uneven signal distribution, with several areas experiencing weak signal strength and substantial speed degradation. This study was conducted to resolve these issues by mapping coverage areas and installing additional access points using NetSpot and WiFi Analyzer. The study employed the Action Research method, consisting of Diagnosing, Action Planning, Action Taking, Evaluating, and Learning. The results demonstrate that installing supplementary access points effectively improved Wi-Fi coverage across previously underserved areas. Post-installation measurements revealed excellent overall signal distribution, ensuring strong, stable, and consistent connectivity for users within the Archive Building of PT PLN (Persero) UIP SUMBAGSEL.